Powerful proofreading skills : tips, techniques and tactics - Smith, Debra A. (Crisp Pub. Menlo ParkUS, 1994)
Defines proofreading and distinguishes between proofreading and editing. Provides methodology for producing error-free proofread copies of documents and correspondence. Explains how to proofread for accuracy in grammar, usage, and numbers. Provides basic rules of English grammar and usage, and, for expressing numbers. Practice in proofreading is provided throughout.